DESIGN AND DEVELOPMENT OF A WEB-BASED MENU ORDERING SYSTEM AT KOPITAWA CAFE USING QR CODE - Erwin Sudirman; Zulhajji, Zulhajji; Muis Mappalotteng, Abdul (Journal of Electrical Engineering and Informatics, 2025)
This study aims to determine the design outcomes and testing results of the menu ordering system at Kopitawa Café.The research employed an R&D (Research and Development) approach and utilized the waterfall development model, incorporating data collection techniques such as observation, interviews, and questionnaires. Based on the study's findings, a web-based menu ordering system for Kopitawa Cafe was successfully designed and developed using QR codes. The system was tested following the ISO/IEC 25010 standard, which includes eight testing aspects. The results indicate that the designed system is feasible and ready for use. This study aims to design and develop a web-based menu ordering system at Kopitawa Cafe using QR Code technology. The research method follows Research and Development (R&D) with the Waterfall development model, including requirements analysis, system design, implementation, verification, and maintenance. The system was tested based on ISO/IEC 25010 standards, covering eight key aspects: functionality suitability, usability, reliability, performance efficiency, maintainability, compatibility, portability, and security. The results indicate that the developed system achieved 100% success in functionality testing, with a usability score of 91.03%, categorized as "excellent". Performance testing using GTMetrix resulted in a 57% (Grade C) score, with a 5.2-second loading time. Portability testing confirmed that the system operates smoothly on various devices and operating systems. Security testing with Quttera verified that the system meets basic security standards. However, this study has some limitations, including the need for further optimization of system performance, dependency on Firebase, which may impact scalability, and security aspects that require additional penetration testing. Future research should focus on improving system speed, enhancing security features, and exploring alternative database solutions.